Analysis of the Mediation Effect of Organizational Creative Climate on the Relationship of Self-Efficacy to Innovative Work Behavior - Indajang, Kevin; Romy, Elly; Sembiring, Lenny Dermawan; Chandra, Erbin; Sudirman, Acai (International Journal of Business, Law, and Education, 2023)
the potential for failure. Most business actors just starting their businesses experience the stigma of fear of failure, which can hinder innovation. In the context of MSMEs in the Lake Toba tourist area, the relationship between organizational creative climate (OCC), Self-Efficacy, and innovative work behavior can be very relevant. This research aims to analyze the mediating effect of organizational creative climate on the influence of self-efficacy on innovative work behavior. The results of this study confirm that self-efficacy has a significant effect on organizational creative climate. Organizational creative climate has a significant influence on innovative work behavior. The results further confirm that organizational creative climate can mediate the relationship between self-efficacy and innovative work behavior. The practical implications of this research can be the basis for advocacy to the government and related parties to provide further support to MSMEs in the region. This can involve policies that support the formation of an organizational creative climate and increase Self-Efficacy among MSME players.